1954
DOI: 10.1002/gj.3350010406
|View full text |Cite
|
Sign up to set email alerts
|

The ordovician succession near llanystwmdwy caernarvonshire

Abstract: A section in the River Dwyfach shows the main Snowdon Lavas and Tuffs to be overlain by a series of sediments and tuffs with a Longvillian fauna near the base. These sediments are followed by black graptolitic shales belonging to the Dicranograptus clingani and Pleurograptus linearis zones overlain by Ashgill mudstones with Phillipsinclla parabola.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1961
1961
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A similar graptolite fauna from the Pen-y-Garnedd Shale of Montgomeryshire was thought to represent a level high in the linearis Biozone by Elles (in King, 1923, p. 492) and Pugh (1923, p. 518) regarded graptolites from the Nod Glas of the Corris area as representing the boundary between the clingani and linearis biozones. A similar assessment of graptolites from broadly equivalent strata near Criccieth, North Wales, was made by J. C. Harper (1956). The situation is not yet resolved and the position of the boundary shown in Figure 1 is to be taken as provisional.…”
Section: Ashgill Seriesmentioning
confidence: 92%
“…A similar graptolite fauna from the Pen-y-Garnedd Shale of Montgomeryshire was thought to represent a level high in the linearis Biozone by Elles (in King, 1923, p. 492) and Pugh (1923, p. 518) regarded graptolites from the Nod Glas of the Corris area as representing the boundary between the clingani and linearis biozones. A similar assessment of graptolites from broadly equivalent strata near Criccieth, North Wales, was made by J. C. Harper (1956). The situation is not yet resolved and the position of the boundary shown in Figure 1 is to be taken as provisional.…”
Section: Ashgill Seriesmentioning
confidence: 92%
“…(1997) did not record any linearis Biozone assemblages from the Llanilar–Rhayader area, but Williams et al . (2003 a ) recognized equivalents of the linearis Biozone at Frongoch, southwest of Cardigan, and records of Climacograptus styloideus at Llanystumdwy suggest that the linearis Biozone may be present in North Wales (Harper, 1956). Exact correlation between the base of the Ashgill Series as defined in the UK, and the British graptolite biostratigraphical sequence cannot as yet be made, as the Welsh record is poor, and the Lower Ashgill of Scotland is rarely graptolitic (Rushton, 1990).…”
Section: Ordovicianmentioning
confidence: 99%
“…The Ordovician strata along the adjacent River Dwyfach was described by Harper (1956), who showed that pre-Longvillian to Ashgill strata were present. The Phillipsinella parabola Beds were the highest fossiliferous Ashgill beds, although some 18.5 m of unfossiliferous greenish-grey slates with thin siltstone laminae occur above them (Roberts, 1967).…”
Section: Relationship Of the Llanystumdwy Outlier To The Surrounding mentioning
confidence: 97%